2018
DOI: 10.1111/jace.16240
|View full text |Cite
|
Sign up to set email alerts
|

Sintering behavior of bimodal iron nanopowder agglomerates

Abstract: The most important issue in the processing of nanoscale metal powders is whether the metal nanopowder can be fully consolidated into ultra‐fine‐ or nano‐grained powder metallurgy parts by pressureless sintering. This paper focuses on the sintering behavior of bimodal iron (Fe) nanopowder agglomerates by considering their microstructure and densification kinetics. During the sintering, bimodal Fe nanopowder compacts underwent discontinuous shrinkage behavior until they neared full density. Three contributions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…The values obtained appear to be in agreement with the activation energy of the grain-boundary self-diffusion of pure iron, which is in the range of 53 to 80 kJ/mol. [23] Song et al [20] also observed similar activation energy values while studying the sintering behavior of bimodal iron nanopowder agglomerates.…”
Section: Densification Kineticsmentioning
confidence: 61%
See 1 more Smart Citation
“…The values obtained appear to be in agreement with the activation energy of the grain-boundary self-diffusion of pure iron, which is in the range of 53 to 80 kJ/mol. [23] Song et al [20] also observed similar activation energy values while studying the sintering behavior of bimodal iron nanopowder agglomerates.…”
Section: Densification Kineticsmentioning
confidence: 61%
“…Sintering kinetics under non-isothermal conditions is more correct than under isothermal conditions. [20] Densification also occurs during the initial stages of the heating process, and therefore, it is difficult to determine whether changes occur during heating or isothermal holding. [21] To investigate the densification kinetics and the dominant mechanism, the non-isothermal sintering was thus analyzed.…”
Section: Densification Kineticsmentioning
confidence: 99%
“…There are different isoconversional methods to evaluate E at different degrees of conversion, α. The Ozawa, Flynn and Wall method uses a plot of log β verses 1 T plot whose slope gives E for a particular α [13]. There are other methods like the Friedman method and the nonlinear Vyazovkin method which have their own set of advantages or disadvantages [14,15].…”
Section: Theorymentioning
confidence: 99%
“…The use of metal nanopowder instead of the conventional micrometre-sized powder for the powder metallurgical process route in order to manufacture near fully dense material has been of great interest for high performance applications [1]. The use of nanopowder however reduces the green density of conventionally die-pressed compacts owing to poor compressibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation